Specificity and mechanism of TonB-dependent ferric catecholate uptake by Fiu - Yang, Taihao; Zou, Ye; Ng, Ho Leung; Kumar, Ashish; Newton, Salete M.; Klebba, Phillip E. (Frontiers in Microbiology, 2024)
We studied the Escherichia coli outer membrane protein Fiu, a presumed transporter of monomeric ferric catecholates, by introducing Cys residues in its surface loops and modifying them with fluorescein maleimide (FM). Fiu-FM bound iron complexes of the tricatecholate siderophore enterobactin (FeEnt) and glucosylated enterobactin (FeGEnt), their dicatecholate degradation product Fe(DHBS)2 (FeEnt*), the monocatecholates dihydroxybenzoic acid (FeDHBA) and dihydroxybenzoyl serine (FeDHBS), and the siderophore antibiotics cefiderocol (FDC) and MB-1. Unlike high-affinity ligand-gated porins (LGPs), Fiu-FM had only micromolar affinity for iron complexes. Its apparent KD values for FeDHBS, FeDHBA, FeEnt*, FeEnt, FeGEnt, FeFDC, and FeMB-1 were 0.1, 0.7, 0.7, 1.0, 0.3, 0.4, and 4 μM, respectively. Despite its broad binding abilities, the transport repertoires of E. coli Fiu, as well as those of Cir and FepA, were less broad. Fiu only transported FeEnt*. Cir transported FeEnt* and FeDHBS (weakly); FepA transported FeEnt, FeEnt*, and FeDHBA. Both Cir and FepA bound FeGEnt, albeit with lower affinity. Related transporters of Acinetobacter baumannii (PiuA, PirA, BauA) had similarly moderate affinity and broad specificity for di- or monomeric ferric catecholates. Both microbiological and radioisotopic experiments showed Fiu’s exclusive transport of FeEnt*, rather than ferric monocatecholate compounds. Molecular docking and molecular dynamics simulations predicted three binding sites for FeEnt*in the external vestibule of Fiu, and a fourth site deeper in its interior. Alanine scanning mutagenesis in the outermost sites (1a, 1b, and 2) decreased FeEnt* binding affinity as much as 20-fold and reduced or eliminated FeEnt* uptake. Finally, the molecular dynamics simulations suggested a pathway of FeEnt* movement through Fiu that may generally describe the process of metal transport by TonB-dependent receptors.